IDENTIFIKASI PERUBAHAN PENGGUNAAN LAHAN DI KAPANEWON KALASAN DENGAN PENDEKATAN KERUANGAN - Maria Gloria De Aroyo Tania Mali; Amithya Irma Kurniawati; Candra Ragil (KURVATEK, 2023)
Abstract - Land use change is the change from the previous land use function to another function, one of which is the change from agricultural land to non-agricultural land. Land use change in Kapanewon Kalasan is driven by various community activities. This is due to the rapid population growth and the location of Kapanewong Kalasan, which is the center of crowds near Yogyakarta city. It is in Central Java and is traversed by the Yogyakarta-Surakarta road. The purpose of the study on land use change in Kapanewon Kalasan by spatial approach is to (1) identify land use change from 2010 to 2020, and (2) identify land use change based on the type of spatial approach for a specific time. The research method is a quantitative method by used spatial process analysis with the overlay technique on ArcGIS ArcGIS. The findings show that over the past decade, Kapanewon Kalasan land use increased by 78.1%, land use designated for dry farming increased by 23.1%, paddy field use increased by 90.5%. Overlay results show that many agricultural drylands are being converted to paddy fields and residential areas, thus the increase in agricultural dryland use is small. Keywords: Land use change, Spatial approach, Spatial process analysis, ArcGis, Overlays